RESOLUTION OF THE PANEL OF EXPERTS ON «THE PHARMACEUTICAL PROVISION OF PSORIATIC ARTHRITIS PATIENTS WITH THE TARGETED SYNTHETIC DISEASE-MODIFYING ANTIRHEUMATIC DRUG APREMILAST AS TABLETS» (Научно-практическая ревматология)
.